Neuroprotective effects of umbelliferone and esculetin in a mouse model of Parkinson's disease. Issue 3 (27th November 2012) - Subramaniam, Sudhakar R.; Ellis, Elizabeth M.
Abstract The production of reactive oxygen species and mitochondrial dysfunction in the brain are both associated with the progression of several neurodegenerative diseases, including Parkinson's disease. These characteristics are also observed when rodents are exposed to the neurotoxin 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP), a compound that causes nigrostriatal dopaminergic neurotoxicity and that has been used previously for assessing the effectiveness of neuroprotective agents. In this study, the neuroprotective effects of two coumarins, umbelliferone and esculetin, against MPTP‐induced neurotoxicity were examined in C57BL/6J mice. The results show that dietary administration of umbelliferone and esculetin significantly attenuated MPTP‐induced neurotoxicity in the substantia nigra pars compacta but not striatum, as measured by tyrosine hydroxylase staining. Both coumarins also prevented an MPTP‐induced increase in nitrosative stress as measured by 3‐nitrotyrosine immunoreactivity and also maintained glutathione levels in MPTP‐exposed mice as well as in cell lines exposed to the metabolite 1‐methyl‐4‐phenylpyridinium. Umbelliferone and esculetin also prevented MPTP‐dependent caspase 3 activation, an indicator of apoptosis, but did not inhibit monoamine oxidase activity. This is the first time that the neuroprotective capabilities of these coumarins have been demonstrated, and the results indicate that umbelliferone and esculetin can protect against MPTP‐induced neurotoxicity in the mouse. These compounds can cross the blood–brain barrier, so their effectiveness indicates that they have the potential to protect in neurodegenerative disease such as Parkinson's disease. © 2012 Wiley Periodicals, Inc.